TANGGUNG JAWAB NOTARIS PENSIUN YANG MASIH MENJALANKAN AKTIVITAS SEBAGAI NOTARIS - , MUHAMMAD IKHWAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to find how a deed have the force of law as the authentic deed and to know the result laws against deed made by a notary who has retired and to find out the result of letter or certificate made by the notary who has retired to the contents of deed. This research is the juridical normative made through the library research data obtained from the study of qualitative analyzed and the results of the analysis are presented in descriptive. The results showed that the deed made by and or before a notary have a perfect proof strength as an authentic deed if the form of deed in accordance with the established by the legislation made before a notary and notary deed office area created. Due to laws against the deed of made by the notary who has retired, the certificate does not have the power of proof as the authentic deed but only have the power as deed under the hand and can be categorized as an act of false or fake letters, because the deed made by a notary who has retired. A notary who has retired but still make deed can be subject to criminal sanctions as referred to in article 263 and 378 KUHCriminal and may be subject to civil penalties the payment of compensation in accordance with article 1365 Juncto article 1246 KUHCivil, if it can be proven have losses arising from the fake deed. And as a result of the law against any deed made by notary deed of retirement against the contents of that the agreement upon an agreement both sides can continue to run and can be canceled if his legitimate terms agreement that is in the article 1320 KUHCivil have been met with the risk that deed only had power as a deed under the hand only and that the risk in half by the respective parties, in the new testament portion of the walk and there was a problem then it can file a lawsuit to court by one party to such deed shall canceled because made by a notary who has retired.